Kajian Hukum Tata Negara terhadap Penyimpangan Kewenangan Mahkamah Konstitusi dalam Putusan Nomor 112/PUU-XXI/2023 - Gunawan Widjaja; Songga Aurora Abadi; Sukh Pawen Jit Kaur (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The Constitutional Court's decision No. 112/PUU-XX/2022, which changed the term of office for the leadership of the Corruption Eradication Commission (KPK) from four years to five years, has sparked controversy in the realm of Indonesian constitutional law. The Constitutional Court, which is supposed to act as a negative legislator, is considered to have exceeded the limits of its authority by establishing new norms in its decision. This research aims to analyze whether the action is a form of deviation of the Constitutional Court's authority referring to the 1945 Constitution and Law Number 24 of 2003 concerning the Constitutional Court. This research uses a normative juridical method with a descriptive-analytical approach through a literature study of regulations, scientific journals, and other legal sources. The research findings indicate that the Constitutional Court not only declared Article 34 paragraph (1) of the KPK Law contrary to the 1945 Constitution, but also stipulated a direct change in the term of office to five years, including for the current KPK leadership. This action is considered a form of judicial activism that deviates from the principle of separation of powers and the principle of non-retroactivity of law. In conclusion, the Constitutional Court's decision creates legal uncertainty, opens space for politicization of the judiciary, and sets a negative precedent in Indonesia's constitutional system. Therefore, it is necessary to reaffirm the limits of the authority of the Constitutional Court in order to remain within the framework of constitutional law that upholds the principle of checks and balances at all times.